PHENOLIC SYSTEM IN THE PROTECTION OF PLANTS CANNABIS SATIVA L. FROM HEAVY METALS IN SYRDARYA REGION (Scientific journal of the Fergana State University, 2023)
This article discusses the results of a study of the content of heavy metals (Hg, Pb, Cr, Sn, Ni, Cu, Fe, Mn, Zn) in plant (CannabissativaL) and soil samples made in saline soils of Syrdarya region. The reaction of the antioxidant defense system of plants (phenols and flavonoids) was also specific, both an increase and a decrease in the antioxidant status were observed, which is due to the different resistance of plants to the action of pollutants. In some cases, correlations were found between the content of heavy metals and the level of phenols and flavonoids, which indicates the cause of the biochemical stress of plants.